Anti‐aging and hydration efficacy of a cross‐linked hyaluronic acid microstructure patch. Issue 3 (17th April 2019) - Lee, Ye Jin; Kim, Hak Tae; Lee, Woo Jin; Chang, Sung Eun; Lee, Mi Woo; Choi, Jee Ho; Won, Chong Hyun
Abstract: This study evaluated the safety and efficacy of biodegradable microstructure patches composed of cross‐linked hyaluronic acid (CLHA). A primary skin irritation test showed that the CLHA patches were not an irritant, whereas a clinical study showed that application of single CLHA patches significantly improved skin hydration at the periorbital region for 3 days and at the nasolabial fold for 6 days. Patch application also improved superficial wrinkles at the periorbital region for 3 days and at the nasolabial fold for 1 day. The absence of side effects indicated that application of these CLHA microstructure patches is both safe and convenient for moisturization and anti‐wrinkle effects.